Prepared to die: A reflection on responding appropriately to complex questions - Kendall, Stewart (Aotearoa New Zealand Social Work, 2016)
This article is a reflective journey of my own ‘in-the-moment’ response to a client’s question about how to appropriately respond to a terminal diagnosis. A brief summary is provided of the way I responded to this situation, followed by an exploration of other ways that I may have been able to respond that could have been more appropriate to the client’s needs. My reflection proceeds to incorporate general ideas of how social workers can respond to challenging questions and situations.